Divergent neuroimmune signatures in the cerebrospinal fluid predict differential gender-specific survival among patients with HIV-associated cryptococcal meningitis - Okurut, Samuel; Boulware, David R.; Okafor, Elizabeth; Rhein, Joshua; Kajumbula, Henry; Bagaya, Bernard S.; Bwanga, Freddie; Olobo, Joseph O.; Manabe, Yukari C.; Meya, David B.; Janoff, Edward N. (Frontiers in Immunology, 2023)
Survival among people with HIV-associated cryptococcal meningitis (CM) remains low, particularly among women, despite the currently optimal use of antifungal drugs. Cryptococcus dissemination into the central nervous system (brain, spinal cord, and cerebrospinal fluid, (CSF)) elicits the local production of cytokines, chemokines, and other biomarkers. However, no consistent diagnostic or prognostic neuroimmune signature is reported to underpin the risk of death or to identify mechanisms to improve treatment and survival. We hypothesized that distinct neuroimmune signatures in the CSF would distinguish survivors from people who died on antifungal treatment, and who may benefit from tailored therapy. We considered baseline clinical features, CSF cryptococcal fungal burden, and CSF neuroimmune signatures with survival at 18 weeks among 419 consenting adults by "gender" (168 females and 251 males by biological sex defined at birth). Survival at 18 weeks was significantly lower among females than among males (47% vs.59%, respectively, hazard ratio HR=1.4, (95% confidence interval, CI: 1.0 to 1.9; p=0.023)). Unsupervised principal component analysis (PCA) demonstrated divergent neuroimmune signatures by gender, survival, and intragender-specific survival. Overall, females had lower levels of PD-L1, IL-1RA, and IL-15 than males (all p<0.028). Female survivors compared with those who died expressed significant elevations in levels of CCL11 and CXCL10 chemokines (both p=0.001), as well as increased Th1, regulatory, and Th-17 cytokines (all p<0.041). In contrast, male survivors expressed lower levels of IL-15 and IL-8 compared with males who died (p<0.044). Survivors of both genders demonstrated a significant increase in the levels of immune regulatory IL-10. In conclusion, the lower survival among females with cryptococcal meningitis was accompanied by distinct differential gender-specific neuroimmune signatures. These female and male intragender-specific survival-associated neuroimmune signatures provide potential targets for interventions to advance therapy to improve the low survival among people with HIVassociated cryptococcal meningitis.